Logic Fault Diagnosis of Hidden Delay Defects - Holst, Stefan; Kampmann, Matthias; Sprenger, Alexander; Reimer, Jan Dennis; Hellebrand, Sybille; Wunderlich, Hans-Joachim; Weng, Xiaoqing (IEEE International Test Conference (ITC'20), November 2020)

Built-in Test for Hidden Delay Faults - Kampmann, Matthias; A. Kochte, Michael; Liu, Chang; Schneider, Eric; Hellebrand, Sybille; Wunderlich, Hans-Joachim (IEEE Transactions on Computer-Aided Design of Integrated Circuits and Systems (TCAD))
Marginal hardware introduces severe reliability threats throughout the life cycle of a system. Although marginalities may not affect the functionality of a circuit immediately after manufacturing, they can degrade into hard failures and must be screened out during manufacturing test to prevent early life failures. Furthermore, their evolution in the field must be proactively monitored by periodic tests before actual failures occur. In recent years small delay faults have gained increasing attention as possible indicators of marginal hardware. However, small delay faults on short paths may be undetectable even with advanced timing aware ATPG. Faster-than-at-speed test (FAST) can detect such hidden delay faults, but so far FAST has mainly been restricted to manufacturing test.

Design For Small Delay Test - A Simulation Study - Kampmann, Matthias; Hellebrand, Sybille (Microelectronics Reliability)

Optimized Constraints for Scan-Chain Insertion for Faster-than-at-Speed Test - Kampmann, Matthias; Hellebrand, Sybille
Keywords: WORKSHOP

Extending Aging Monitors for Early Life and Wear-Out Failure Prevention - Liu, Chang; Schneider, Eric; Kampmann, Matthias; Hellebrand, Sybille; Wunderlich, Hans-Joachim (27th IEEE Asian Test Symposium (ATS'18))

X-tolerante Prüfzellengruppierung für den Test mit erhöhter Betriebsfrequenz - Kampmann, Matthias; Hellebrand, Sybille
Keywords: WORKSHOP

Design-for-FAST: Supporting X-tolerant compaction during Faster-than-at-Speed Test - Kampmann, Matthias; Hellebrand, Sybille (20th IEEE International Symposium on Design & Diagnostics of Electronic Circuits & Systems (DDECS'17))

X Marks the Spot: Scan-Flip-Flop Clustering for Faster-than-at-Speed Test - Kampmann, Matthias; Hellebrand, Sybille (25th IEEE Asian Test Symposium (ATS'16))

Optimized Selection of Frequencies for Faster-Than-at-Speed Test - Kampmann, Matthias; A. Kochte, Michael; Schneider, Eric; Indlekofer, Thomas; Hellebrand, Sybille; Wunderlich, Hans-Joachim (24th IEEE Asian Test Symposium (ATS'15))

Effiziente Auswahl von Testfrequenzen für den Test kleiner Verzögerungsfehler - Hellebrand, Sybille; Indlekofer, Thomas; Kampmann, Matthias; Kochte, Michael; Liu, Chang; Wunderlich, Hans-Joachim
Keywords: Workshop